Self-Cross-Linked Polymer Nanogels: A Versatile Nanoscopic Drug Delivery Platform - Ryu, Ja-Hyoung; Chacko, Reuben T; Jiwpanich, Siriporn; Bickerton, Sean; Babu, R. Prakash; Thayumanavan, S (Journal of the American Chemical Society, 2010)
Nanoscopic vehicles that stably encapsulate drug molecules and release them in response to a specific trigger are of great interest due to implications in therapeutic applications, especially for cancer therapy. For this purpose, we have synthesized highly stable polymeric nanogels, in which the kinetics of guest molecule release can be fine-tuned by control over cross-linking density. The polymer nanogel precursor is based on a random copolymer that contains oligoethyleneglycol (OEG) and pyridyldisulfide (PDS) units as side-chain functionalities. By introducing variations into the precursor polymer, such as molecular weight and the relative percentages of hydrophilic OEG units and hydrophobic PDS functionalities, we have achieved significant control over nanogel size. We show that the noncovalently encapsulated guest molecules can be released in response to a redox trigger, glutathione (GSH). Stability of dye encapsulation inside the nanogels and tunability in the release of guest molecules have been demonstrated through in vitro fluorescence resonance energy transfer (FRET) experiments. We show in vitro doxorubicin delivery into breast cancer cells (MCF-7) with nanogels of different cross-linking density to demonstrate that it plays a key role in the stable encapsulation of hydrophobic drug molecules and the cell-uptake efficiencies.